A management framework for the implementation of policies for industrial ecology, Part II: a competitive bidding process. (18th October 2006) - Indrianti, Nur; Matsuoka, Shinobu; Muraki, Masaaki
One strategy to implement Industrial Ecology (IE) is to utilise industrial waste streams as alternative sources of other needed materials. This paper is concerned with a competitive bidding process for converter selection to support the implementation of tax and subsidy policy that promotes secondary material converted from industrial waste, as a substitute for virgin material. With regard to the government's problem in determining the quota to allocate and the converter's difficulties in building strategies, we propose a two-stage sealed-bid format and rating approach using a performance index for converter selection and quota allocation. We describe a bidding procedure that can be efficient and effective for both the government and the converters participating in the bidding process. Our analysis shows that the implementation of a two-stage bidding format can improve competition among bidders, leading to a better achievement of the goal of the policy.